(untitled) (Journal of Pharmaceutical Negative Results, 2022)
This article, first of all, shows the role of cotton in our daily life, its importance in various sectors of the economy. It is also paid attention to the etymology of the words "pahta" in Uzbek and "cotton" in English. In this work, the use of the lexeme cotton in English and Uzbek languages ​​in different meanings is revealed, they are compared in the two languages, attention is paid to their similarities and differences. The meanings of expressions related to the word cotton are explained with the help of specific examples.